Experimental effects of an interactive program for improving reading comprehension in a rural population of primary grade 5 - Sotelo, Noemí (2012)
We report the results of an experimental study with two randomized groups pre and post-test, which seeks to determine the effects of the implementation of an interactive program on the reading comprehension of children in 5th grade in a rural area of the province of Yungay in the Department of Ancash. The analysis of data collected through the Reading Comprehension Test of Linguistic Complexity Progressive (CLP) Alliende, adapted by Delgado and processed with SPSS v. 18, to conclude that the interactive reader used in the experimental group shows a significant increase in reading comprehension scores compared with those obtained by the control group.